Challenges in Implementing Land Certificates at the Ministry of Agrarian Affairs and Spatial Planning - Kurnia Rheza Randy Adinegoro; Dani Iswahyuni (Sekolah Tinggi Pertanahan Nasional, 2023)
This research discusses the challenges of implementing electronic land certificates as a digital transformation step in the Ministry of Agrarian and Spatial Planning (Ministry of ATR/BPN). As technological developments require an organization to transform, public organizations are no exception. This study takes into account the Ministry of ATR/BPN's digital transformation of the public sector, particularly the implementation of electronic land certificates. The Ministry of ATR/BPN continues to follow developments with the times, but of course this is not easy because in its implementation it faces many challenges. The method used in this research is a normative juridical research method with a data collection model based on library research. This research tries to describe it descriptively so that it will become an illustration of the implementation of digital land certificates. And in the next discussion, we will discuss the challenges and solutions that have been taken by the Ministry of ATR/BPN. The author concludes that, in the future, electronic land certificates will be a necessity that cannot be avoided for various important reasons. Electronic certificates can also reduce the number of disputes, conflicts, and land cases. However, the process requires sufficient time because technology transfer requires skilled and adequate human resources.